Cannabis and Brain: Disrupting Neural Circuits of Memory - Uddin, Md. Sahab; Sheshe, Sadeeq Muhammad; Islam, Israt; Mamun, Abdullah Al; Hussein, Hussein Khamis; Labu, Zubair Khalid; Ahmed, Muniruddin (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Cannabis is a federally controlled substance, it’s very familiar to many but its neurobiological substrates are not well-characterized. In the brain, most areas prevalently having cannabinoid receptors have been associated with behavioral control and cognitive effects due to cannabinoids. Study over the last several decades suggested cannabinoids (CBs) exert copious oftentimes opposite effects on countless neuronal receptors and processes. In fact, owing to this plethora of effects, it’s still cryptic how CBs trigger neuronal circuits. Cannabis use has been revealed to cause cognitive deficits from basic motor coordination to more complex executive functions, for example, the aptitude to plan, organize, make choices, solve glitches, remember, and control emotions as well as behavior. Numerous factors like age of onset and duration of cannabis use regulate the severity of the difficulties. People with the cannabis-linked deficiency in executive functions have been found to have trouble learning and applying the skills requisite for fruitful recovery, setting them at amplified risk for deterioration to cannabis use. Exploring the impacts of cannabis on the brain is imperative. Therefore the intention of this study was to analyze the neuropsychological effects and the impact of CBs on the dynamics of neural circuits, and its potential as the drug of addiction.